Snow in the changing sea-ice systems. Issue 11 (November 2018) - Webster, Melinda; Gerland, Sebastian; Holland, Marika; Hunke, Elizabeth; Kwok, Ron; Lecomte, Olivier; Massom, Robert; Perovich, Don; Sturm, Matthew
Abstract Snow is the most reflective, and also the most insulative, natural material on Earth. Consequently, it is an integral part of the sea-ice and climate systems. However, the spatial and temporal heterogeneities of snow pose challenges for observing, understanding and modelling those systems under anthropogenic warming. Here, we survey the snow–ice system, then provide recommendations for overcoming present challenges. These include: collecting process-oriented observations for model diagnostics and understanding snow–ice feedbacks, and improving our remote sensing capabilities of snow for monitoring large-scale changes in snow on sea ice. These efforts could be achieved through stronger coordination between the observational, remote sensing and modelling communities, and would pay dividends through distinct improvements in predictions of polar environments. This Perspective provides an overview of the snow–sea ice systems in the Arctic and Antarctic, offering insight on how current uncertainties can be reduced, and future challenges met, to improve understanding of polar climate change.